Algicidal effects of free-amine water-soluble chitosan to marine harmful algal species - Park, Seong-Cheol; Choi, Changyong; Jeong, Gyeong-Won; Lee, Hyun-Su; Choi, Sun-Ju; Kim, Won-Seok; Nah, Jae-Woon (Journal of industrial and engineering chemistry (Seoul, Korea), 2016)
Chain forms and morphological changes in C. polykrikoides with chitosans. After addition of chitosans (0.4mg/mL) to C. polykrikoides suspension, the plate was incubated for 6h. (a) Control; (b) LMWISC; (c) LMWSC-1; (d) LMWSC-2; (e) LMWSC-3; (f) LMWSC-4. Harmful algal blooms (HABs) commonly cause significant damage to aquatic systems due to toxin production and depletion of oxygen. In this study, the low molecular weight water-soluble chitosan (LMWSC) was investigated as a new algicidal compound by first investigating the potential of LMWSC in selective combating HABs. The LMWSCs disrupted algal cell and chloroplast membranes within 1h against HABs, leading to efflux of the intracellular components. For co-cultivation of harmful and harmless algal, LMWSC selectively kill the harmful algal. Based on these results, LMWSC is a promising novel material for harmful algal bloom control.